2017
DOI: 10.18203/issn.2455-4529.intjresdermatol20164404
|View full text |Cite
|
Sign up to set email alerts
|

A study of 200 cases of pityriasis versicolor: the distribution of age, gender, blood group, lesion morphology, hemoglobin levels, cholesterol levels and diabetic status

Abstract: INTRODUCTIONPityriasis versicolor is the most important and most common Malassezia-associated superficial skin infection.1 It is particularly prevalent in tropical and subtropical regions like India. It is an opportunistic pathogen which infects skin when its commensal round yeast form transforms to the pathologic mycelial form. This transformation occurs due to a shift in the relationship between the human skin and resident yeast flora. 2In lesional skin the most common species are M. globosa, M. restricta, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The similar observation was reported among the participants in the 2 nd and 3 rd decade of life. 15,29 Sharma et al 8 and Badri et al 30 had also reported similar findings in their studies. The probable causes of higher incidence of PV among 21-30 years age group may be increased sebum production and a high level of physical activity leading to excess sweating which provide a favourable environment for the proliferation of lipophilic yeast to cause PV.…”
Section: Figure: 3 Morphological Appearance Of Malassezia Species In ...supporting
confidence: 57%
“…The similar observation was reported among the participants in the 2 nd and 3 rd decade of life. 15,29 Sharma et al 8 and Badri et al 30 had also reported similar findings in their studies. The probable causes of higher incidence of PV among 21-30 years age group may be increased sebum production and a high level of physical activity leading to excess sweating which provide a favourable environment for the proliferation of lipophilic yeast to cause PV.…”
Section: Figure: 3 Morphological Appearance Of Malassezia Species In ...supporting
confidence: 57%